Blockchain and Associated Legal Issues for Emerging Markets - Salmon, John (International Finance Corporation, Washington, DC, 2019)
Blockchain, or distributed ledger technology (DLT), is a tamper-evident and tamper-resistant digital ledger implemented in a distributed fashion.1 This emerging technology, which enables direct transactions within a ledger without need for a central authority or trusted intermediary, has the potential to re-engineer economic models and enable the creation of markets and products previously unavailable or unprofitable across emerging markets. However, in considering the potential benefits of blockchain, organizations must also consider the associated risks and how they can be managed. These risks include jurisdictional challenges, crypto assets, privacy and data protection, double spending, and distributed denial-of-service (DDoS) attacks. Several risks have been identified and overcome at similar innovative leaps in the recent past, including the commercialization of the Internet and cloud computing. It is essential that enterprises understand all risks inherent in blockchain systems, including being able to clearly identify who is accountable and legally responsible.